Mysticism in Jonathan Edwards’s Theology of Spirituality: A Comparison between Edwards’s and Bernard of Clairvaux’s Understanding of Union and Communion with Christ - Kim, Song (Jonathan Edwards studies, 2021)
The concepts of union and communion with Christ are significant elements in Jonathan Edwards’s theology of spirituality. Since such concepts contain mystical elements, it is worthwhile to examine Edwards’s mystical ideas in order to understand his view of union and communion. Moreover, Edwards often uses language reminiscent of Bernard of Clairvaux, such as “sweet,” when he describes the concept of communion with Christ. Despite these similarities, no research has focused on comparing the perspectives of Edwards and Bernard, especially those concerning union and communion with Christ. This article analyzes Edwards’s view of union and communion with Christ as it relates to Bernardine mysticism. Furthermore, this article examines the continuity and discontinuity between the two theologians by providing a historical and theological assessment of the strands of Bernardine mysticism in Edwards’s thought.